Analysis of the Impact of Minimarkets on Convenience Stores on HKSN Street, Banjarmasin - Risnawati Risnawati; Rina Rina (PT. Hanken SUkses Jaya, 2023)
This study aims to find out the impact before and after the existence of a minimarket on grocery stores in Jalan HKSN Banjarmasin. This type of exploratory descriptive research with data collection techniques using interviews, questionnaires, and documentation. Quantitative analysis technique using crosstabulation with SPSS. The qualitative technique used data reduction, data presentation, and conclusion. The number of samples in this study was 15 grocers. The results of the study show that traders who have an impact on the existence of minimarkets have experience of more than 10 years plus the uncertain changes in market prices are the cause of the difficulty in competing with minimarket companies that have large capital and for new traders or trading experience that does not last too long, minimarkets are not too much impact on their results.